PENGEMBANGAN PROGRAM MEMBACA DI PERPUSTAKAAN: SALAH SATU KOMPONEN PENTING MENJADI MURID MELEK INFORMASI (INFORMATION LITERATE STUDENT)) - Agustina, Susanti (Jurnal Kajian Informasi dan Perpustakaan, 2013)
Learning library as the implementation of user education programs. Elementary school, school to school instead of working. Because students will go to school, then it should have the power to learn good. Before the entrance pupil at the level of information literacy, fundamental thing that is important implanted student interests and reading culture since the early entry into the system. The school library should be made good. Furthermore, to form a good reading habit can through the library learning program called "Know Reader". The goal, first technically skilled students know the information and to sort and select information in the library; secondly, to safeguard the assets of the library; Third, condition the students read and used to reading. Including the value of learning libraries into the local curriculum includes a written assessment report cards of students, exhibition of books in the school library every week, an award for academicians who borrowed the most books every month, tells the story hanging way, it makes the students love to read. At the elementary school level which would be built three, first learning culture, both learning skills, and the three basic skills that can be achieved through daily habituation.Pembelajaran perpustakaan sebagai implementasi dari program pendidikan pemakai. Sekolah Dasar, sekolah untuk sekolah bukan bekerja. Karena murid akan melanjutkan sekolah, maka harus mempunyai daya belajar yang baik. Sebelum murid masuk pada tingkat melek informasi, hal mendasar yang penting ditanamkan yaitu minat dan budaya baca murid sejak dini yang masuk ke dalam sistem. Perpustakaan sekolah harus dibuat bagus. Selanjutnya, untuk membentuk minat baca yang baik dapat melalui program pembelajaran perpustakaan bernama "Kenal Pustaka". Sasarannya, pertama secara teknis murid mengetahui informasi dan terampil memilah serta memilih informasi di perpustakaan; kedua, dapat menjaga aset perpustakaan; ketiga, mengondisikan para murid membaca dan terbiasa membaca. Memasukkan nilai pembelajaran perpustakaan ke dalam kurikulum muatan lokal termasuk penilaian tertulis dalam raport murid, pameran buku di perpustakaan sekolah setiap minggu, penghargaan bagi sivitas akademika yang meminjam buku terbanyak setiap bulannya, berkisah dengan cara menggantung ceritanya, semua itu membuat murid gemar membaca. Pada jenjang Sekolah Dasar yang hendak dibangun ada tiga, pertama budaya belajar, kedua keterampilan belajar, dan ketiga keterampilan dasar yang dapat dicapai melalui pembiasaan sehari-hari.